Blockchain on the rise: A global overview of adoption, trends, and market applications - Torres, Danilo; Leal, Esmeide; Leal, Nallig; Ramos, Fabián; Baquero, Andrea; Sáenz, Carlos Díaz (Edelweiss Applied Science and Technology, 2025)
This study analyzes the role of blockchain technology in the digital transformation of businesses, focusing on its adoption, sectoral applications, challenges, investment trends, and integration with emerging technologies such as artificial intelligence (AI). The research employs a technology surveillance methodology in its analytical phase, supported by a documentary review of 69 sources published between 2017 and 2025. The findings reveal that blockchain has evolved beyond its original use in cryptocurrencies and is increasingly applied in finance, healthcare, logistics, education, and public administration. Key benefits identified include enhanced traceability, operational efficiency, and transparency. However, several barriers persist, such as technological infrastructure limitations, high implementation costs, regulatory uncertainty, and a shortage of specialized talent. The study also highlights a growing convergence of blockchain and AI, as well as accelerated adoption among small and medium-sized enterprises (SMEs) and in emerging markets. The conclusions position blockchain as a strategic enabler of business transformation, with strong potential to reshape business models and increase competitiveness. As a practical implication, the study recommends implementing adoption strategies that address investment, talent development, and legal frameworks to fully leverage blockchain’s long-term impact in digital markets.